From Scrubs to Scrolling: Healthcare Professionals on Douyin - Li, Xinna (AoIR Selected Papers of Internet Research, 2026)
Short video platforms are reshaping health communication, yet how healthcare professionals use them to present their expertise in a digital space governed by both entertainment-driven engagement metrics and regulatory constraints remains understudied. This study examines how verified healthcare professionals use Douyin, China’s leading short video platform, to engage in health communication. Through content analysis of 130 highly engaged videos and 58 professionals’ homepages, this study investigates the characteristics of the healthcare professionals on Douyin, how they present themselves, and what strategies they use to balance medical credibility with Douyin’s entertainment-driven nature.